Engineered Glycosidases for the Synthesis of Analogs of Human Milk Oligosaccharides - Nekvasilová, Pavlína; Hovorková, Michaela; Mészáros, Zuzana; Petrásková, Lucie; Pelantová, Helena; Křen, Vladimír; Slámová, Kristýna; Bojarová, Pavla (International journal of molecular sciences, 2022)
Enzymatic synthesis is an elegant biocompatible approach to complex compounds such as human milk oligosaccharides (HMOs). These compounds are vital for healthy neonatal development with a positive impact on the immune system. Although HMOs may be prepared by glycosyltransferases, this pathway is often complicated by the high price of sugar nucleotides, stringent substrate specificity, and low enzyme stability. Engineered glycosidases (EC 3.2.1) represent a good synthetic alternative, especially if variations in the substrate structure are desired. Site-directed mutagenesis can improve the synthetic process with higher yields and/or increased reaction selectivity. So far, the synthesis of human milk oligosaccharides by glycosidases has mostly been limited to analytical reactions with mass spectrometry detection. The present work reveals the potential of a library of engineered glycosidases in the preparative synthesis of three tetrasaccharides derived from lacto-N-tetraose (Galβ4GlcNAcβ3Galβ4Glc), employing sequential cascade reactions catalyzed by β3-N-acetylhexosaminidase BbhI from Bifidobacterium bifidum, β4-galactosidase BgaD-B from Bacillus circulans, β4-N-acetylgalactosaminidase from Talaromyces flavus, and β3-galactosynthase BgaC from B. circulans. The reaction products were isolated and structurally characterized. This work expands the insight into the multi-step catalysis by glycosidases and shows the path to modified derivatives of complex carbohydrates that cannot be prepared by standard glycosyltransferase methods.
Keywords: oligosacharidy; Glycoside Hydrolases; substrátová specifita; enzymatic synthesis; mateřské mléko; Glycosyltransferases; Humans; mutagenesis; human milk oligosaccharide; novorozenec; Substrate Specificity; Oligosaccharides; glykosyltransferasy; glykosidhydrolasy; glycosidase; lidé; Milk, Human; Bifidobacterium bifidum; Infant, Newborn